The Correlation Of Nurse Caring With The Implementation Of SBAR Communication During Patient Handover At Private Hospital In Medan - Nurlela Petra Saragih; Maria Magdalena Saragi R; Almina Rospitaria Tarigan; Eka Isranil Laily; Elfrida Nainggolan (International Journal of Health Engineering and Technology, 2025)
Patient safety is fundamental to the quality of healthcare services, with effective communication serving as its core foundation. The patient handover process remains the most vulnerable period for medical errors, necessitating the accurate and comprehensive transfer of critical information. To mitigate this inherent risk, the structured communication model SBAR (Situation, Background, Assessment, Recommendation) is employed, ensuring that vital information is conveyed concisely and with focus This study utilized an analytical descriptive approach with a cross-sectional design to examine the relationship between nurse caring and the implementation of SBAR communication during handover. The research sample consisted of 32 inpatient unit nurses selected via purposive sampling. Data collection involved a structured questionnaire to measure the level of nurse caring (36 statements) and an observation sheet to assess compliance with SBAR elements (20 statements). The majority of respondents were aged >35 years (72%), held a Bachelor's/Ners education (63%), and were female (81%). The results indicated that the majority of nurse caring was categorized as less effective (75%), and the implementation of SBAR communication was also predominantly deemed less effective (62%). The chi-square statistical test yielded a -value of , confirming a highly significant relationship between nurse caring and the implementation of SBAR communication during handover in the inpatient setting. This finding reinforces the conclusion that integrating caring into SBAR communication practice is a crucial component for enhancing the quality and safety of nursing care.